Análisis del consumo horario residencial de agua potable del Cantón Guano - Llamuca Hernández, María Paula (2023)
Guano, located in Ecuador, is composed of eleven parishes, with La Matriz being the largest residential settlement and having a 71.4% coverage of potable water service for its inhabitants. It is supplied and served through three distribution networks connected to their respective reservoir tanks, namely, Lluishi Tank, La Inmaculada Tank, and Barrios Altos Tank. The population is categorized and stratified into 3 socioeconomic strata, namely, B, C, and D (Cáceres & Rubio, 2015). This study aims to analyze how the consumption of potable water is influenced by both hourly consumption patterns and the characteristics of each network and socioeconomic stratum, through the hourly measurement of 79 meters for a period of 7 days-24 hours. The modeling curves and maximum and minimum hourly consumption variation coefficients (kh) were obtained and compared with those set out in the CPE INEN 5 1992 standard. The hourly consumption variation coefficient used in the design of this network was 2.30, which the standard suggests using in the absence of studies that determine a specific kh for the network. At the end of this study, the maximum kh found was 2.93, which exceeds the recommended value in the standard. The maximum hourly flow rates were 61.35 l/h in Barrios Altos, 151.21 l/h in Lluishi, and 110.81 l/h in La Inmaculada, with an average flow rate of 66.99 l/h in La Matriz.Key words: consumption curve, consumption patterns, hourly flow, consumption coefficient